Effect of pH and organic substrate on growth and activities of ammonia-oxidizing bacteria - DWI AGUSTIYANI; HARTATI IMAMUDDIN; ERNI NUR FARIDAH; OEDJIJONO OEDJIJONO (Society for Indonesian Biodiversity, 2004)
The physiological character, especially the effect of pH and organic substrate on the growth and activity of some ammoniaoxidizing bacteria was carried out. The results show that eight out of twenty isolates have ability to reduce ammonium, two of them i.e. isolate AOB1 and AOB2 could reduce more than 90% of ammonium. The growth and activity to reduce ammonium to nitrite was attained optimum at pH 7-8. From the result also indicated that the growth and activity of both isolate AOB1 and AOB2 were higher on the organic carbon (acetate)-containing media. This finding indicated that both of isolate AOB1 and AOB2 were heterotrophic ammonia-oxidizing bacteria.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: organic substrate, acetate, ammonia-oxidizing bacteria, ammonium, nitrite.